DOMESTIC PREFERENCE PROVISIONS FOR INDONESIAN ELECTRICITY INFRASTRUCTURE PROJECTS FUNDED BY FOREIGN LOANS - Anggita Tridiani Sirait; Djumikasih; Budi Santoso (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The purpose of this study is to analyze the potential inconsistency of the domestic preference provisions in ESDM Ministerial Regulation No. 11 of 2024 with the principles of the Regulation for ADB Borrowers and its legal implications on electricity infrastructure projects funded by foreign loans. This research method is normative juridical with a legislative approach, an analytical approach, and a conceptual approach. The results show that the domestic preference provisions in ESDM Ministerial Regulation No. 11 of 2024 strengthen the use of domestic products in electricity projects funded by foreign loans, but have the potential to conflict with the principles of fairness and transparency in the Procurement Regulations for ADB Borrowers. Nationally, this policy is legitimate and supports economic independence, but internationally it can raise issues of inconsistency with the WTO principles of non-discrimination and national treatment and affect the credibility of the procurement process.